2018
DOI: 10.3126/jmmihs.v4i1.21144
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of poisoning cases in Manmohan Memorial Teaching Hospital

Abstract: Background: Poisoning is one of the leading causes of morbidity and mortality in Nepal and also a major public health problem worldwide. It needs specific epidemiological surveillance to determine the extent and pattern of poisoning of a place, and to take preventive measures. Hence this study is aimed to explore the demographic, etiological, and clinical characteristics of poisoning cases of MMTH and to assess the effect of variables such as age, sex, and agent of poisoning frequency.Methods: A retrospective,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
(7 reference statements)
1
2
0
Order By: Relevance
“…The current findings announced that most patients were married. This was similar to the results observed by Sunny et al (2019) and Bajracharya et al (2018) who explained these results by the fact that they bear the bulk of the family's obligations, may be constantly stressed out, and are more likely to be exposed to OPC.…”
Section: Discussionsupporting
confidence: 91%
“…The current findings announced that most patients were married. This was similar to the results observed by Sunny et al (2019) and Bajracharya et al (2018) who explained these results by the fact that they bear the bulk of the family's obligations, may be constantly stressed out, and are more likely to be exposed to OPC.…”
Section: Discussionsupporting
confidence: 91%
“…OP insecticides are a common means of self-harm in the LMIC because they are very widely used in agriculture [7]. The common OPs currently used in Nepal include dichlorvos, chlorpyrifos, dimethoate and malathion [9,[22][23][24]. A hospitalbased study from five major hospitals across Nepal in 2002 showed that OP compounds were the most common agent for self-poisoning, methyl parathion and dichlorvos being the key pesticides involved [25].…”
Section: Discussionmentioning
confidence: 99%
“…Patients were most commonly: women (n ¼ 2533, 61.3%; unknown gender n ¼ 15), of the Janajati ethnic group ((n ¼ 1063 27.7%) [16], and aged 16-30 years ((n ¼ 2350, 57.5%). Median age of patients was 25 years (IQR 19-35), with a small difference between sexes (male: 27 ; female 24 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Pesticide Self-poisoning Among Patients Presenting To Hospitalsmentioning
confidence: 99%